0116 Evidence of dose-response in the causation of mesothelioma from environmental exposure. (21st August 2017) - Ferrante, Daniela; Magnani, Corrado; Mirabelli, Dario
Abstract : We investigated the relation between cumulative asbestos exposure and pleural malignant mesothelioma (PMM) in areas with environmental asbestos exposure from human activities and asbestos material in place, using our studies and a literature review. Casale Monferrato (NW Italy) presents high PMM incidence caused by asbestos contamination at work and in the general environment from the asbestos cement Eternit plant that operated until 1986. A population-based case-control study including PMM diagnosed between January 2001 and June 2006 (200 PMM and 348 controls) observed among subjects never occupationally exposed a dose response relationship consistent with that caused by occupational exposures, based on individual assessment of environmental and domestic exposures. ORs were 3.8 (CI 95% 1.3 to 11.1) for cumulative exposure from ≥0.1 to<1 f/ml-year, 14.8 (5.7 to 38.6) for ≥1–<10 f/ml-y and 23.3 (CI 95% 2.9 to 186.9) for >10 f/ml-y (reference: background level of asbestos exposure). ORs of about 2, statistically significant, were observed for domestic exposure and for living in houses near buildings with large asbestos cement parts. Similar trends were observed in other studies that explored the dose response relationship in the low dose range (Iwatsubo et al 1998, Rodelsperger et al 2001, Lacourt et al 2014). PMM risk increased with cumulative asbestos exposure in analyses limited to subjects non-occupationally exposed and in the environmental exposure range. These results provide indication of risk associated with common sources of environmental exposure and are highly relevant for the evaluation of residual risk after the cessation of asbestos industrial use.